(untitled) (Transactions of the Association of European Schools of Planning, 2022)
The UK government’s ‘Levelling Up’ agenda represents the latest attempt to address long-standing inter-regional socio-economic disparities in England. This paper assesses how the Levelling Up The UK White Paper, published in early 2022, frames the problem of interregional inequality and the potential of the proposed solutions contained within the paper to address the problem. We argue that the Levelling Up agenda as currently framed is likely to be too spatially vague to achieve meaningful reductions in the level of interregional inequality in England, and suggest that any attempts to improve the economic performance of regions outside of London and the South East should focus on the fortunes of England’s ‘second-tier’ city-regions. Using Liverpool City Region as a case study area, we discuss three key themes included in the white paper and identify some areas where additional policy focus will be required to meet the UK government’s aspirations.